What is #int (2x^3-3x^2-4x-3 ) / (-6x^2+ 3 x -4 )dx#?

Answer 1

#-x^2/6+x/3+19/18ln|(1/2sqrt(29/2))/sqrt(6x^2-3x+4)|-13/(2sqrt(87))*tan^(-1) (4sqrt(3/29)(x-1/4))+const.#

First we should get in the numerator a polynomial of a grade inferior than the denominator's

By long division:

#" "2x^3-3x^2-4x-3" "#|#" "-6x^2+3x-4# #-2x^3+x^2-4/3x" "#|____ _____#" "-1/3x+1/3# #" "-2x^2-16/3x-3# #" "2x^2-x+4/3# #" "# _______ #" "-19/3x-5/3=-1/3(19x+5)#
So the expression becomes #=1/3int (-x+1)dx-1/3*1/6int(19x+5)/(x^2-x/2+2/3)dx#
Dealing with #=int(19x+5)/(x^2-x/2+2/3)dx# Since #(x-1/4)^2=x^2-x/2+1/16# and #2/3-1/16=29/48=(1/4sqrt(29/3))^2# We can make
#x-1/4=1/4sqrt(29/3)*tan y# => #dx=1/4sqrt(29/3)*sec^2 y*dy# Now let's find how many units of #(x-1/4)# there are in the denominator #" "19x+5" "#|#" "x-1/4# #-19x+19/4" "#|____ _____#" "19# #" "39/4#
So the partial expression becomes #=19int ((1/4sqrt(29/3)tan y)(1/4sec^2 y))/(1/16*29/3sec^2 y)dy+39/4int (1/4sqrt(29/3))/(1/16*29/3sec^2 y)dy# #=-19ln|cos y|+39sqrt(3/29)y# But #tan y = sqrt(3/29)(4x-1)# => #siny =sqrt(3/29)(4x-1)cosy# And #sin^2y+cos^2y=1# => #(3/29(16x^2-8x+1)+1)cos^2 y=1# => #(48x^2-24x+32)/29*cos^2 y=1# => #cos y=(1/2sqrt(29/2))/sqrt(6x^2-4x+8# Then the partial expression becomes #=-19ln|(1/2sqrt(29/2))/sqrt(6x^2-4x+8)+39sqrt(3/29)tan^(-1) (sqrt(3/29)(4x-1))#
Back to the main expression: #=-x^2/6+1/3-1/18[-19ln|(1/2sqrt(29/2))/sqrt(6x^2-4x+8)+39sqrt(3/29)tan^(-1) (sqrt(3/29)(4x-1))]# #=-x^2/6+x/3+19/18ln|(1/2sqrt(29/2))/sqrt(6x^2-3x+4)|-13/(2sqrt(87))*tan^(-1) (4sqrt(3/29)(x-1/4))+const.#
One step further: simplifying The result above is good enough, but the constant part of the logarithm can be absorbed by the general constant: #=-x^2/6+x/3+19/18[ln(1/2sqrt(29/2))-(1/2)ln|6x^2-3x+4|]-13/(2sqrt(87))*tan^(-1) (4sqrt(3/29)(x-1/4))+const.#
#=-x^2/6+x/3-19/36ln|6x^2-3x+4|-13/(2sqrt(87))*tan^(-1) (4sqrt(3/29)(x-1/4))+const.#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the integral of the given expression (\frac{2x^3 - 3x^2 - 4x - 3}{-6x^2 + 3x - 4}) with respect to (x), you can use polynomial long division to simplify the expression first. Once simplified, you can then integrate each term separately.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7